MicroRNAs as Novel Biomarkers of Deployment Status and Exposure to Polychlorinated Dibenzo-p-Dioxins/Dibenzofurans. Issue 8 (August 2016) - Woeller, Collynn F.; Thatcher, Thomas H.; Van Twisk, Daniel; Pollock, Stephen J.; Croasdell, Amanda; Hopke, Philip K.; Xia, Xiaoyan; Thakar, Juilee; Sime, Patricia J.; Mallon, Timothy M.; Utell, Mark J.; Phipps, Richard P.
Abstract : Objective: To determine if service members deployed to locations with open air burn pits have different serum microRNA (miRNA) profiles after deployment compared with length-of-service matched, non-deployed individuals. We also tested for correlations between miRNA and serum levels of Polychlorinated Dibenzo-p-Dioxins/Dibenzofurans (PCDD/PCDFs). Methods: MiRNAs were isolated and quantified by PCR array. Groups were analyzed for differences in miRNA expression. Correlations between serum miRNA and PCDD/PCDFs were assessed with a linear regression model. Results: Several miRNAs were differentially expressed after deployment and a partially overlapping set of miRNAs were identified between deployed and non-deployed individuals. Significant correlations between miRNAs and PCDD/PCDFs were identified. Conclusions: Serum miRNA levels show a link between deployment to locations with open burn pits and environmental exposures that can take place during deployment.